It's not just what we encode, but how we encode it: associations between neuroticism and learning. - Byrom, N; Murphy, R (2013)
OBJECTIVE: Neuroticism is a strong predictor of future mental health problems. The informativeness of this association has been questioned because of the limited understanding of the mechanisms underlying Neuroticism. In this article the authors extend our understanding of the association between information processing and Neuroticism. METHOD: Two independent studies involving separate sets of college students (N = 89 and N = 33), use self-rated Neuroticism scores to compare individuals' ability to learn simple and more complex discriminations, between simple shapes and words presented alone and in compound. RESULTS: Neuroticism was found to be associated with differences in learning to discriminate simple stimuli from compounds containing the same simple stimuli. Individuals with high levels of Neuroticism appeared to process compounds of stimuli as whole units even when this ceased to be an effective strategy for learning. In contrast, individuals with lower levels of Neuroticism performed better with discriminations that could be solved while learning about separate stimuli, rather than compounds. CONCLUSIONS: The authors discuss possible mechanisms of learning identified by these tasks and consider what implications their observations have for an understanding of the relationship between Neuroticism and mental health problems.